Enhanced wedelolactone content in in vitro-raised genetically uniform Wedelia chinensis under the influence of CuSO4 - Swami, Ravi Kant; Nimker, Shwetanjali; Narula, Alka; Farooqi, Humaira (Frontiers in Plant Science, 2023)
In the present study, we addressed the imperative for potent anticancer agents through Wedelia chinensis, a medicinal plant abundant in the robust anti-hepatotoxic and anti-tumor compound wedelolactone. Hindrances in conventional propagation methods due to crosspollination and habitat degradation prompted us to pioneer in vitro rapid multiplication using plant tissue culture. Optimal outcomes were attained employing Murashige and Skoog medium supplemented with IBA (0.5 mg/l) and KN (5.0 mg/l), yielding 97.67% shoot regeneration and 81.67% rooting from nodal explants. Transplanted plantlets exhibited a 92% survival rate. We established a wedelolactone extraction protocol using Toluene: Ethyl acetate: Formic acid (5:4:1) for HPTLC analysis, trailblazing wedelolactone quantification and 2C DNA analysis in W. chinensis via flow cytometry. Experiments under heavy metal stress with CuSO 4 unveiled physiological responses, with peak wedelolactone content (193.90 μg/gm dw) in vitro at 75 μM CuSO 4 , surpassing in vivo levels (89.95 μg/gm dw) by 116%. By pioneering successful in vitro rapid multiplication and enhanced wedelolactone content, we bridge a critical gap in the conservation and production of this medicinal plant.Our findings not only offer a sustainable means of propagation but also present a viable strategy for elevating the yield of potent bioactive molecules like wedelolactone, holding immense promise for the development of novel therapeutic interventions and addressing the pressing healthcare challenges of our time.